Pengaruh Video Edukasi Range of Motion terhadap Pengetahuan dan Kemampuan Keluarga Merawat Pasien Stroke - Putri Zafira; Fitri Anita; Resa Livia Nica (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2026)
Stroke is one of the leading causes of disability and mortality worldwide. In Indonesia, stroke contributes to 11.2% of disability cases and 18.5% of national mortality, with a prevalence of 8.3 per 1,000 population. This condition requires continuous care, including the role of family members in performing Range Of Motion (ROM) exercises. Educational videos as audiovisual media are considered effective in improving family understanding and skills. This study aimed to determine the effect of ROM educational videos on improving the knowledge and abilities of families in caring for stroke patients at Advent Hospital, Bandar Lampung City, in 2026. This quantitative study used a One Group Pretest–Posttest design using purposive sampling with a sample of 29 families of stroke patients. Data were collected using a knowledge questionnaire and an ability observation checklist before and after the educational video intervention, and were analyzed using univariate and bivariate analysis. The results showed an improvement in family knowledge and abilities after the intervention, with a p-value of 0.000 < 0.05, indicating a significant effect. It was concluded that ROM educational videos are effective in improving family knowledge and abilities and can be used as a practical and easily understood health education medium. Practically, video-based education can be integrated into hospital discharge education programs to support families in continuing stroke patient care at home.